KLASIFIKASI SPASIAL PENUTUP LAHAN DENGAN DATA SAR DUAL-POLARISASI MENGGUNAKAN NORMALIZED DIFFERENCE POLARIZATION INDEX DAN FITUR KERUANGAN DARI MATRIK KOOKURENSI (SPATIAL LAND COVER CLASSIFICATION USING DUAL-POLARIZATION SAR DATA BASED ON NORMALIZED DIFFERENCE POLARIZATION INDEX AND SPATIAL FEATURES FROM CO-OCCURRENCE MATRIX) - Dony Kushardono (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2012)
In this study, the land cover classification method using the spatial information features of co-occurence matrix and Normalized Difference Polarization Index (NDPI) data from dual polarization SAR Data was proposed. The spatial information features are used as input of supervised classification, and to get the performance of the proposed method, land cover classification was conducted with SAR C-band and L-band satellite data of Envisat ASAR and ALOS PALSAR. The results of the study are, the size of window on the SAR image to get the spatial information features of co-occurence matrix and the use of additional NDPI data are giving effect to the accuracy of classification results. At the test area in Siak Riau Province which have 7 classes of land use, the optimum window size for co-occurence matrix is 7pixel x 7pixel for ASAR data which has 75m spatial resolution, and more than 9pixel x 9pixel for PALSAR data which has 10m spatial resolution. The addition of the co-occurence matrix information of NDPI data can improve the classification of accuracy up to 2%. Key words: Spasial land cover classification, Dual polarization SAR, NDPI, Co-occurrence matrix